Contribution to the fuel surcharge in Bogotá for road development (2013)
This paper presents the current situation of the implementation of the surcharge on gasoline as a tribute to improve the road network in Bogotá DC and quality of the transport system in 2012 and the first quarter of 2013. It also seeks to identify the impact of public management in making decisions of the leaders in the management of these resources and their implications for the future in order to achieve development plan for Bogotá DC The results allow to propose alternatives to study the revenue generated by the tax are optimized and fulfill their reason for creation of value in the quality of life of citizens.